Charged-particle multiplicity measurement in proton-proton collisions at √s=7 TeV with ALICE at LHC - Aamodt, Kenneth; Angelov, Venelin; Busch, Oliver; Glässel, Peter; Grajcarek, Robert; Herrmann, Norbert; Klein, Jochen; Mercado Pérez, Jorge; Oyama, Ken; Pachmayer, Yvonne C.; Schicker, Rainer; Schweda, Kai; et al. (The European physical journal. C, Particles and fields, 2010)
The pseudorapidity density and multiplicity distribution of charged particles produced in proton–proton collisions at the LHC, at a centre-of-mass energy s√=7 TeV, were measured in the central pseudorapidity region |η|<1. Comparisons are made with previous measurements at s√=0.9 TeV and 2.36 TeV. At s√=7 TeV, for events with at least one charged particle in |η|<1, we obtain dNch/dη=6.01±0.01(stat.)+0.20−0.12(syst.). This corresponds to an increase of 57.6%±0.4%(stat.)+3.6−1.8%(syst.) relative to collisions at 0.9 TeV, significantly higher than calculations from commonly used models. The multiplicity distribution at 7 TeV is described fairly well by the negative binomial distribution.
*The ALICE Collaboration: K. Aamodt, V. Angelov, O. Busch, P. Glässel, R. Grajcarek, N. Herrmann, J. Klein, J. Mercado Pérez, K. Oyama, Y. Pachmayer, R. Schicker, K. Schweda, H.K. Soltveit, J. Stachel, S. Vallero, B. Windelband (und sehr viele weitere Personen]
Im Titel steht der Buchstabe s unter dem Wurzelsymbol
Gesehen am 14.11.2022